Integrated value management - Gomez, Peter (International Thomson Business Press, 1999)
This book is one of the first to deal with raising the value of a company by exploiting all its internal and external potentials. Integrated Value Management takes a holistic approach to corporate strategy. This is unusual in management books, which tend to bias themselves towards one particular paradigm or field of management. It deliberately presents a European perspective against the more commonly found American approach to management, and backs this up through the selection of case studies which illustrate the theories. The book exemplifies theory through easily understood practical examples emphasising application